Relasi Huruf Muqatta'ah dan Integrasi Pemahaman Surah dalam Al-Qur'an - Khoirun Niat (Lajnah Pentashihan Mushaf Al-Qur'an, 2020)
This article is aimed at knowing the structure of huruf muqatta'ah and its significance toward the unity of surahs in the Qur'an. This study becomes important because hitherto the concept of the unity of the Qur'anic surahs has not made the huruf muqatta'ah as the part of that surah yet. The contribution expected is that the readers can have an integral understanding on the Qur’anic surah without neglecting the huruf muqatta'ah that become the beginning of the surah. Literature review of this study takes the main data from the verses of Surah al-Baqarah which are initiated by the structure of huruf muqatta'ah, alif-lam-mim. The approach used is structural analysis of Levi-Strauss, that is to look for the relations among the elements to find the transformation in the text. This study found the relation of symbolic structure between alif-lam-mim and the grand theme of the surah al-Baqarah. The structure of surah al-Baqarah can be understood as the interactions of the three kinds of people namely the believer (mu'min), hypocrite (munafiq) and infidel (kafir). Alif becomes the symbol of the believer; lam becomes the symbol of hypocrite (munafiq), and mimbecomes the symbol of infidel (kafir). The interaction of the three can be described in imprecise triangle model. It is from this model that the significance of alif-lam-mim to understand the Surah al-Baqarah can be known integrally